2022
DOI: 10.3389/fphys.2022.979283
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature and donor piglet age on the transcriptomic profile and energy metabolism of myoblasts

Abstract: Rapid climate change is associated with frequent extreme heat events and the resulting thermal stress has consequences for the health, welfare, and growth of farm animals. The aim of this study was to characterize the transcriptional changes and the effects on energy metabolism in proliferating porcine myoblasts derived from piglets of different ages, representing differences in thermoregulatory abilities, and cultivated below (35°C) and above (39°C, 41°C) the standard cultivation temperature (37°C). Satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Heat stress impaired mitochondrial biogenesis and function, thereby reducing the expression of PAX7, MYOD, MYF5, MYOG and MYHC, which might be the Frontiers in Cell and Developmental Biology frontiersin.org reason for the inhibition of proliferation and differentiation in myoblasts. Metzger et al (2022) demonstrated that the biological processes and signaling pathways correlated with proliferation were downregulated in porcine myoblasts under heat stress (41 °C) (Metzger et al, 2022), and Chen et al ( 2020) reported that heat stress (42 °C) interfered the myogenic differentiation via changing the expression of MYOD, MYOG and MYHC (Chen et al, 2020), which is consistent with our results. Cell migration, proliferation and differentiation have profound effects on the development of skeletal muscle (Ye et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Heat stress impaired mitochondrial biogenesis and function, thereby reducing the expression of PAX7, MYOD, MYF5, MYOG and MYHC, which might be the Frontiers in Cell and Developmental Biology frontiersin.org reason for the inhibition of proliferation and differentiation in myoblasts. Metzger et al (2022) demonstrated that the biological processes and signaling pathways correlated with proliferation were downregulated in porcine myoblasts under heat stress (41 °C) (Metzger et al, 2022), and Chen et al ( 2020) reported that heat stress (42 °C) interfered the myogenic differentiation via changing the expression of MYOD, MYOG and MYHC (Chen et al, 2020), which is consistent with our results. Cell migration, proliferation and differentiation have profound effects on the development of skeletal muscle (Ye et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…We observed the increased expression levels of HSP60, HSP70 and HSP110 in the heat-stressed myoblasts during proliferation and differentiation, which indicated that the myoblasts suffered from severe heat stress. Metzger et al (2022) reported that heat stress (41 °C) upregulated the expression of HSP70 in porcine myoblasts (Metzger et al, 2022). The development of skeletal muscle is an extraordinarily complicated and delicate process, which includes the proliferation and differentiation of the satellite cells (Reed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al [ 48 ] found that focal adhesion was closely associated with the growth of embryonic skeletal muscle in chickens. Metzger et al [ 49 ] discovered that cytokine–cytokine receptor interaction was involved in myoblasts proliferating derived from piglets of different ages. We have found no previous studies on the relationship between Salmonella infection and skeletal muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins cooperate to establish the muscle phenotype by regulating proliferation, irreversible cell cycle arrest, and regulated transcription of sarcomeric and muscle-specific genes for differentiation and sarcomere formation [13]. Our previous research highlighted the differential expression of numerous genes in porcine myoblast cultures subjected to heat or cold stress, with these transcripts linked to a range of biological processes and signaling pathways [14]. Notably, the majority of molecular changes occurred at the control temperature of 37 • C, which is the standard cultivation temperature for porcine muscle cell cultures and appropriate for comparing myoblast cells from piglet donors that are still developing their thermoregulatory capabilities under temperature stress [14].…”
Section: Introductionmentioning
confidence: 99%